Inside knowledge: incarcerated people on the failures of the American prison - Larson, Doran (New York University Press, 2024)
"In Inside Knowledge incarcerated people step forth as the primary witnesses and documentarians of the American prison's historical and ongoing defeat of the four cardinal rationales for the legal caging of human beings: rehabilitations, deterrence, containment, and retribution"--